Assessment Of Oral Health Status Among Sugar Factory Workers Of Barwani District M.P - Patidar, Prafful; Gupta, Dhaman; Nagarajappa, Sandesh; Mishra, Prashant; Sontakke, Shantanu; Singh, Robin (Journal of Neonatal Surgery, 2025)
Inroduction: Occupational environments have a profound impact on both general and oral health. Exposure to sugar and its byproducts might influence oral health of the sugar factory workers. Hence the aim of the study is to assess the oral health status of the sugar factories workers of Barwani district M.P. Methodology: A cross-sectional study was conducted in four private sugar factories located in the Barwani district. Using multistage random sampling, a total of 200 sugar factory workers. Out of 200 study participants, 140 frontline and 60 administrative workers were selected for participation. The oral health status of the workers was assessed using the WHO Oral Health Assessment Form (2013). Data analysis was performed using SPSS version 21. Descriptive statistics, including mean, standard deviation, and proportions, were calculated for each clinical parameter. For intergroup comparisons, Student’s T-test and Chi-square analysis were employed Result: The mean DMFT (Decayed, Missing, and Filled Teeth) score for production line workers was 1.02 +1.3, while administrative workers had a significantly lower mean score of 0.63+1.35 and the difference was found to be statistically significant (p = 0.001). The periodontal condition of the study participants was also compromised, with approximately 40% exhibiting bleeding gums, whereas around 20% had periodontal pockets Conclusion: The present study revealed that oral health of sugar factory workers is compromised which primarily due to the exposure of sugar dust. This further indicates a need to educate the factory workers about the oral hygiene habits and oral hygiene maintenance.